Protective Effects of Polydatin on Septic Lung Injury in Mice via Upregulation of HO-1 - Xiao-hui Li (Mediators of Inflammation, 2013)
The present study was carried out to investigate the effects and mechanisms of polydatin (PD) in septic mice. The model of cecal ligation and puncture (CLP-)induced sepsis was employed. Pretreatment of mice with PD (15, 45, and 100 mg/kg) dose-dependently reduced sepsis-induced mortality and lung injury, as indicated by alleviated lung pathological changes and infiltration of proteins and leukocytes. In addition, PD inhibited CLP-induced serum tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) production, lung cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase isoform (iNOS) protein expressions and NF-κB activation. Notably, PD upregulated the expression and activity of heme oxygenase (HO-)1 in lung tissue of septic mice. Further, the protective effects of PD on sepsis were abrogated by ZnPP IX, a specific HO-1 inhibitor. These findings indicated that PD might be an effective antisepsis drug.